Julius Gold collection - Gold, Julius, 1884-1969.; Ziehn, Bernhard, 1845-1912. (1858)
Manuscripts of Gold's theoretical writings, including unpublished translations of and commentaries on the writings of Bernhard Ziehn. Includes correspondence with colleagues and students, among the former Hans Joachim Moser, Lloyd Hibberd, and John Alden Carpenter, and the latter Winthrop Sargent, Frank Fragale, Meredith Willson, and Isaac Stern. Programs, printed music, financial and legal papers, and photographs.
Julius Gold, teacher and musicologist; born Feb. 18, 1884, in St. Joseph, Mo., died Jan. 29, 1969, in California.
Finding aid available in the Library of Congress Performing Arts Reading Room and on the Internet.
Julius Gold Collection, Music Division, Library of Congress.
Keywords: Gold, Julius, -- 1884-1969.; Gold, Julius, -- 1884-1969 -- Autographs; Music theory; Musicians -- Autographs; Ziehn, Bernhard, -- 1845-1912 -- Criticism and interpretation; Musicians -- Correspondence; Moser, Hans Joachim, -- 1889-1967 -- Correspondence; Hibberd, Lloyd -- Correspondence; Carpenter, John Alden, -- 1876-1951 -- Correspondence; Sargeant, Winthrop, -- 1903-1986 -- Correspondence; Fragale, Frank, -- 1894-1955 -- Correspondence; Willson, Meredith, -- 1902-1984 -- Correspondence; Stern, Isaac, -- 1920-2001 -- Correspondence